2011
DOI: 10.1007/s00441-011-1227-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of EMT in renal fibrosis

Abstract: It is clear that the well-described phenomenon of epithelial-mesenchymal transition (EMT) plays a pivotal role in embryonic development, wound healing, tissue regeneration, organ fibrosis and cancer progression. EMTs have been classified into three subtypes based on the functional consequences and biomarker context in which they are encountered. This review will highlight findings on type II EMT as a direct contributor to the kidney myofibroblast population in the development of renal fibrosis, specifically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(205 citation statements)
references
References 177 publications
5
197
1
2
Order By: Relevance
“…The origin of these collagen-forming cells is not always clear, but it has classically been accepted that they derive from tissue-resident fibroblasts; recent evidence suggests that other cell populations (i.e., organ epithelial cells) are also able to generate MFB during EMT induction. Moreover, it is clear that type 2 EMT of epithelial cells from organs undergoing fibrosis results in the ability to produce ECM components [121,122]. For example, MFB in the liver mainly originates from the activation of hepatic stellate cells (HSC) [119]; however, adult hepatocytes that undergo EMT induced by TGF-β can also contribute to the MFB population [123][124][125].…”
Section: Purinergic Signaling Emt and Fibrosismentioning
confidence: 99%
“…The origin of these collagen-forming cells is not always clear, but it has classically been accepted that they derive from tissue-resident fibroblasts; recent evidence suggests that other cell populations (i.e., organ epithelial cells) are also able to generate MFB during EMT induction. Moreover, it is clear that type 2 EMT of epithelial cells from organs undergoing fibrosis results in the ability to produce ECM components [121,122]. For example, MFB in the liver mainly originates from the activation of hepatic stellate cells (HSC) [119]; however, adult hepatocytes that undergo EMT induced by TGF-β can also contribute to the MFB population [123][124][125].…”
Section: Purinergic Signaling Emt and Fibrosismentioning
confidence: 99%
“…9 It is widely accepted in the literature that there are similarities between the development of fi brosis and embryonic morphogenesis, 10 concepts not limited to the lung. 11 Fibulin-1 is produced by lung fi broblasts 12 and has been shown to play a role in the pathophysiology of patients with asthma, 13 a disease characterized in part by airway fi brosis. 14 We reasoned that dysregulated fi bulin-1 expression may be involved in lung diseases with more extensive fi brosis as mechanisms of fi brogenesis are likely to be shared.…”
Section: Fibulin-1 Levels In Tissuementioning
confidence: 99%
“…Hypoxia induces EMT in different kinds of cell. [9][10][11][12] In this study, we found that hypoxia induced EMT in human mesothelial cells (Met-5A cells) and primary-cultured rat peritoneal mesothelial cells. The EMT changes of Met-5A cells were abolished by HIF-1a inhibition.…”
Section: -8mentioning
confidence: 66%
“…[5][6][7][8] Hypoxia contributes to EMT in different kinds of cell, such as malignant cells and renal tubular cells. [9][10][11][12] Hypoxia is also associated with end-stage renal disease, and is a risk factor for cardiovascular events. [13][14][15] However, its roles in the EMT of peritoneal mesothelial cells have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%